Radioembolization of liver metastases from colorectal cancer using yttrium-90 microspheres with concomitant systemic oxaliplatin, fluorouracil, and leucovorin chemotherapy. - Sharma, R; Van Hazel, G; Morgan, B; Berry, D; Blanshard, K; Price, D; Bower, G; Shannon, J; Gibbs, P; Steward, W (2007)
PURPOSE: Liver metastases represent the principal cause of death in patients with advanced colorectal cancer (CRC). Injection of resin microspheres (SIR Spheres)--containing the beta-emitter, yttrium-90--into the arterial supply of the liver can cause radioembolization of metastases. This treatment has not been tested with the radiosensitizing chemotherapy, oxaliplatin, which appears synergistic in the treatment of CRC when combined with fluorouracil and leucovorin (FOLFOX). PATIENTS AND METHODS: A phase I study of SIR-Spheres therapy with modified FOLFOX4 systemic chemotherapy was conducted in patients with inoperable liver metastases from CRC who had not previously received chemotherapy for metastatic disease. Oxaliplatin (30 to 85 mg/m2) was administered for the first three cycles with full FOLFOX4 doses from cycle 4 until cycle 12. The primary end point was toxicity. RESULTS: Twenty patients were enrolled onto the study. Five patients experienced National Cancer Institute (NCI; Bethesda, MD) grade 3 abdominal pain, two of whom had microsphere-induced gastric ulcers. The dose-limiting toxicity was grade 3 or 4 neutropenia, which was recorded in 12 patients. One episode of transient grade 3 hepatotoxicity was recorded. Mean splenic volume increased by 92% following 6 months of protocol therapy. Partial responses were demonstrated in 18 patients and stable disease in two patients. Two patients underwent partial hepatic resection following protocol therapy. Median progression-free survival was 9.3 months, and median time to progression in the liver was 12.3 months. CONCLUSION: The maximum-tolerated dose was 60 mg/m2 of oxaliplatin for the first three cycles, with full FOLFOX4 doses thereafter. This chemoradiation regime merits evaluation in phase II-III trials.